PENGUATAN TATA KELOLA USAHA MELALUI PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS DIGITAL BUMDES KECAMATAN GUNUNG SARI - Indriani, Eni; Inapty, Biana Adha; Martiningsih, Rr. Sri Pancawati (Jurnal Pepadu, 2024)
BUMDes is a village business established by the village government, whose capital ownership and management are carried out by the village government and the community. The administration of financial reports at partner BUMDes is currently identified as not being optimal due to the low competency of human resources. For this reason, the Community Service Team at the Faculty of Economics and Business, Mataram University, feels it is necessary to provide training and assistance related to strengthening business governance through training activities and assistance in preparing digital-based financial reports. Digitalization is the process of transferring media from all forms of printed documents to digital presentation. The application of digitalization makes things easier for business owners because it can reduce the risk of calculation errors, damage, or loss of financial documents, speed up preparation time, and evaluate business financial results wherever they are. The community service partners that will be embraced are BUMDes in Gunung Sari District, West Lombok Regency, totaling 16 BUMDes. This community service activity will run for 6 months, starting from May to October 2023. The service activity starts with preliminary observation activities through field studies of Bumdes in Gunung Sari District and discussions with village facilitators to obtain information about the problems faced by BumDes. The team designed training activities, which were attended by all BumDes managers in Gunung Sari District along with village assistants. During the training activity, the service team presented material related to the preparation of digital-based financial reports and had discussions with participants who conveyed the problems they faced and then strengthened each other by sharing solutions that could be applied to their respective BumDes. Mentoring activities carried out include accompanying Bumdes in training for Bumdes financial staff.